External audit quality and ownership structure: interaction and impact on earnings management of industrial and commercial Tunisian sectors - Amel Kouaib; Anis Jarboui (Journal of Economics, Finance and Administrative Science, 2014)
This article emphasizes the significance of researching the cross effect of using jointly external audit quality and ownership structure over managerial discretion in a largely unexplored, non-Western and emerging context. The analysis is based on a sample of 61 Tunisian firms listed and unlisted on the Tunis Stock Exchange and operating in the industrial and commercial sectors during the period 2007-2011. To provide evidence on this topic, we conduct an empirical examination. First, we examine the effect of external audit quality and ownership structure on the discretionary accruals for the whole sample. We find that only auditor reputation has a negative and significant effect on earnings management. Second, this article provides empirical evidence on the cross effect of external audit quality variables and capital concentration on earnings management. This test suggests that this combination has a negative and significant effect on earnings management in industrial firms but it has a positive and non significant effect in commercial firms. Finally, the third empirical test concerns the combined effect of external audit quality and institutional property on earnings management. We find that the cross effect of this combined relation is negatively and significantly associated with earnings management of industrial firms but it has no significant effect on the earnings management of commercial firms. As for the cross effect of the auditor seniority and the institutional property, it has a positive and a significant effect in the commercial sectors, while, it is positively and non-significantly associated with earnings management of industrial firms. – – Este artículo enfatiza la importancia de investigar el efecto cruzado del uso conjunto de la calidad de la auditoría externa y la estructura propietaria sobre el criterio gerencial, en un contexto emergente no occidental y ampliamente inexplorado. El análisis se basa en una muestra de 61 empresas tunecinas y no cotizadas en la bolsa de Túnez, que operan en sectores industriales y comerciales durante el período 2007-2011. Para aportar evidencia sobre esta cuestión, realizamos un examen empírico. Primeramente, examinamos el efecto de la calidad de la auditoría externa y la estructura propietaria sobre el acumulado discrecional de la muestra en su totalidad. Encontramos que únicamente la reputación del auditor tiene un efecto negativo e importante sobre la gestión de los ingresos. En segundo lugar, este artículo aporta evidencia empírica sobre el efecto cruzado de las variables de calidad de la auditoría externa y la concentración del capital sobre la gestión de los ingresos. Este test sugiere que esta combinación tiene un efecto negativo sobre la gestión de los ingresos en las empresas industriales, aunque presenta un efecto positivo y no significativo en las empresas comerciales. Por último, el tercer test empírico se refiere al efecto combinado de la calidad de la auditoría externa y la propiedad institucional sobre la gestión de los ingresos. Encontramos que el efecto cruzado de esta relación combinada es negativo y está asociado de manera importante a la gestión de los ingresos de las empresas industriales, pero no tiene un efecto significativo sobre la gestión de los ingresos de las empresas comerciales. En cuanto al efecto cruzado de la antigüedad del auditor y la propiedad institucional, tienen un efecto considerable sobre las empresas comerciales, mientras que están asociados a la gestión de los ingresos en las empresas industriales, de modo positivo y no significativo.
Keywords: M42; 330; External audit quality; Ownership structure; Discretionary accruals; Cross effect; Calidad de la auditoría externa; Estructura propietaria; Gestión de ingresos; Acumulado discrecional; Efecto cruzado; Sectores tunecinos